Settling in: Reintroduced Persian Fallow Deer Adjust the Borders and Habitats of Their Home-Range During the First 5 Years Post Release - Maor-Cohen, Mia; Bar-David, Shirli; Dolev, Amit; Berger-Tal, Oded; Saltz, David; Spiegel, Orr (Frontiers in Conservation Science, 2021)
Translocated animals typically find themselves in a novel environment in which they must establish a home range in a manner that will maximize their fitness. We hypothesized that the initial establishment of a home range is followed by adjustments expressed as home range shifting, and occurs as familiarity with the landscape increases, until the home range is stabilized. We studied the process of home range shifting in 42 female Persian fallow deer (Dama mesopotamica) reintroduced into the Galilee, Israel over a period of 2-5 years. We used changes in the degree of home range overlap between consecutive years as an indicator of stabilization. We then compared how the mean percent cover of the key vegetation types (woodland, scrubland and open pastures) differed between the areas abandoned in the first year’s home range and the areas added to the last year’s home range relative to the first (using a weighted paired t-test). We also compared the distribution (using χ2 test of independence and Levene’s test for homogeneity of variance) of %cover of the 3 vegetation types between the first and last year’s home range. The average home range overlap increased over the 5 years following the first release. During the first-year post release, deer avoided open pastures and preferred woodland. In later years deer increase in the % open pastures (weighted t-test: p<0.001) and decreased the % woodland cover (weighted t-test: p=0.07) by abandoning areas with little open pasture and steeper terrain and moving into areas with more open pasture and moderate terrain. Variance of the cover types across individuals increased with time. We conclude that the home ranges of the reintroduced deer stabilized with time. The changes in vegetation and slope are driven by time-dependent changing needs reflecting a tradeoff between refuge and foraging. Our findings suggest that using the initially established home range to determine species preferences can create a misleading picture of what the optimal home range of the species really is. Individual variation in term of preferences can take a few years to be expressed due to the initial high-risk perceived by all individuals.